Simulation of a single-stage evaporator system integrated with a mechanical vapor compressor for concentrating the electrolytic system KNO3 – H2O - Karić, Ervin; Alić, Rejha (Journal of Engineering & Processing Management, 2020)
A simulation of a single-stage evaporator system integrated with a mechanical compressor for a case study (concentrating the electrolytic system KNO3 – H2O) was performed. A mathematical model of the subsystem of a single-stage evaporator, a mechanical compressor, and superheated steam seeding is presented. Microsoft Excel with VBA (Visual Basic for Application) was used to solve the mathematical model. The model was solved by an iterative method where the values of the in-let stream temperature and the salt concentration in the concentrated stream at the evaporator outlet were assumed. The process parameters of the system have been determined. Since the goal of any industrial process is to minimize costs and maximize products, the impact of mean temperature difference changes on saturation water consumption and molar salt content in the concentrated stream was presented. 106.92 kg/h of freshwater are required to obtain 18% by weight of salt in a concentrated stream, while 432.30 kg/h of fresh water are required to obtain 25% by weight of salt in a concentrated stream. Consumption of heating steam ranged from 1760.31 to 4473.4 kg/h depending on the average temperature difference. By increasing the temperature differences from 10 to 25 ◦C, the amount of transferred upper lines increases from 1025 to 2750 kW, which is an advantage of increasing the mean temperature difference. The disadvantage of the larger temperature difference is the increase in the power of the mechanical compressor from 97.02 to 384.12 kW.